Breaking the silence: communication between parents and secondary school adolescents in the context of HIV/AIDs in Zimbabwe: a case of Mkoba high density suburb, Gweru - Mutema, Fungai (Scholarlink research institute journals, 2017)
Most Secondary School adolescents in Zimbabwe are at a very high risk of contracting HIV/AIDS through early and unprotected sexual activities. Though much is being said nationally and internationally about HIV/AIDS, it is a taboo to talk about sexual activities in most Zimbabwean families. This study examines family communication in relation to HIV/AIDS among secondary school adolescents and their parents and is premised on Barnlund’s Transactional Model of Communication which posits that interpersonal communication is a dynamic, process oriented activity in which the two participants are simultaneously sending and receiving messages. A sample of eighty couples and one hundred adolescent boys and girls was purposively selected for purposes of this study. The findings showed that communication at family level is quite problematic though a few indicated that they openly discussed HIV/AIDS related issues. It was also noted that there were gender differences in family communication and also that the parents’ education and religious beliefs determined the level of family communication. This paper goes on to suggest possible ways of ameliorating the challenges in family communication.